LASMI’S STYLE OF SINDHENAN GENDHING TAYUB - Amalya Wijayanti; Danis Sugiyanto (ARTISTIC : International Journal of Creation and Innovation, 2022)
Grobogan Regency is one of the areas where Tayub art is still present. One of the distinctive and unique pesindhèn who produces gendhing recordings is Lasmi. This research focuses on artist Lasmi's creativity in working on her sindhènan (song), typically distinguished by parikan, wiledan, and céngkok. This study uses a qualitative approach by collecting data through observation and in-depth interviews and analyzing data with interactive analysis. The results of this study indicate that working on parikan, which has a comical character, is a rather distinct characteristic of Lasmi's style of working on sindhènan. Lasmi's vocal style in presenting unique céngkok-céngkok can be seen in the gendhing-gendhing Tayub. Sindhènan Lasmi differs from other sindhènan lèdhèk Tayub because it is more luwes (flexible) and prênès.